VORONEZH STATE UNIVERSITY: TRADITIONS, INNOVATIONS AND «LINE OF DEVELOPMENT - Dmitry A. Endovitsky (Высшее образование в России)
The article overviews Voronezh State University's activity in 2015, analyzes the factors shaping the university's development and achievements. It also analyzes the university's traditions and the "Line of development" enabling to keep its leadership in the region.